STUDI LITERATUR: EFEKTIFITAS MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SD - Adinda Silvia Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model on elementary school students’ learning outcomes through a literature review approach. The method employed is a systematic review of 20 relevant national and international journal articles that focus on the implementation of PBL in various elementary-level subjects. The analysis was conducted by identifying common findings, benefits, and impacts of PBL on improving conceptual understanding, critical thinking skills, creativity, and students' learning motivation. The results indicate that PBL consistently provides a positive effect on students' academic performance by presenting real-world problems, fostering active participation, and enhancing collaboration skills that support long-term learning. Therefore, PBL can be recommended as an innovative instructional strategy to improve the quality of elementary school students’ learning outcomes.